OPTIMAL PRODUCTION LOT SIZING WHEN DEMAND IS PROPORTIONAL TO STOCK AND BACKORDER LEVELS - Cheng, Yung-Lung; Wang, Wan-Tsu; Wei, Chun-Chin; Lee, Kuo-Liang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
In this study, we investigate an inventory model where demand and backordering rates are respectively dependent on stock and backorder levels. We consider that there are highest and lowest demand rates during in-stock and stock-out periods. We derive closed-form solutions, and provide a solution procedure to attain the optimal policy. The proposed model is reduced to the traditional economic production quantity models. Finally, numerical examples are provided to illustrate the solution procedure and compare with existing models. Sensitivity analyses of the optimal solution with respect to parameters are presented.